Calcite uranium–lead geochronology applied to hardground lithification and sequence boundary dating. Issue 1 (29th October 2020) - Brigaud, Benjamin; Andrieu, Simon; Blaise, Thomas; Haurine, Frédéric; Barbarand, Jocelyn
Abstract: Hardground discontinuities within carbonate platforms form important stratigraphic surfaces which can be used at basin scale to correlate sequence boundaries. Although these surfaces are commonly used in sequence strati‐graphy, the timing and duration of hardground lithification and the crystallization of early cements remain unexplored. Here, early calcite cements were dated by U‐Pb geochronology for five Jurassic hardgrounds, interpreted as third‐order sequence boundaries, situated within a well‐constrained petrographic, sedimentological and stratigraphic framework. The consistency or the slight deviation between the age of the cements and the stratigraphic age of deposition of the formations illustrate that cementation occurred early in the diagenetic history. The ages obtained on dogtooth cements, replacing aragonite in gastropod shells and pendant cements in intergranular spaces, match those of the standard Jurassic biostratigraphic ammonite Zones, making calcite U‐Pb geochronology a promising method for dating third‐order sequence boundaries of depositional sequences and refining the Jurassic time scale in the future.